Global patent registration as one of mechanisms of managing intellectual property rights - Budyakov, O. (Право и государство, 2016)
This article covers different aspects of the UK patent system, international patent registration process and issues of legal defense of patent. Patents are seen as the most reliable and effective tool of intellectual property (IP) protection, and supported by exhaustive legislation. This article however, using theoretical approaches, applicable laws, historical and current data, as well as practical examples, shows that despite all the advantages of patents, they cannot genuinely protect rights of authors and patent holders. By the results of conducted research the author proposes potential solutions to the recent problems of managing of rights, protected by patents.
Keywords: UK patent system; international patent registration; intellectual property; exclusive right; invention; result of intellectual activity; authors; patent holders; managing patent rights; Research Subject Categories::LAW/JURISPRUDENCE